Numerical Study of Natural Convection in a Cavity Filled with Air and Heated locally from Below - Samir Rahal; A. BEGAR; A. Hamada (International Journal of Applied Methods in Electronics and Computers, 2017)
Heat transfer from discrete heat sources has become a subject of increased interest because of advances in the electronics industry. Increased heat dissipation is the most important outcome of new generation electronic devices which are more and more miniaturized. Large heat flux densities, which need to be dissipated, are obtained as a result of this miniaturization. Electronic cooling has therefore generated increased interest in the analysis of heat transfer in locally heated cavities. Natural convection holds obvious advantages due to its low-cost and noise-free operating conditions. In this work, a numerical study of natural convection, in a cavity filled with air (Prandtl number, Pr = 0.71), which is heated by discrete sources, was carried out. The governing equations were discretized using the finite volume method and a hybrid schema. The resolution was carried out with the Simpler algorithm. Our procedure of simulation was validated by comparing our results with those of other authors. Temperature and velocity fields were obtained. Local and average Nusselt numbers were also calculated. The influence of various parameters (Rayleigh number from 103 to 105, positions of the sources, periods of the variable heat flux) was considered. Correlations between the Nusselt numbers and the various parameters were also obtained.